MBO and Performance Appraisal - Robert E. Chasnoff (Educational Considerations, 1974)
High student motivation, growing self knowledge, and encouragement of innovation are all features of the intern program Dr. Chasnoff describes. He also points out that a major factor in its success is its humanistic setting.